Славянская рецепция Д. Н. Мамина-Сибиряка "На золотом дне" - Удалов, Виктор; Udalov, Vyktor (Волинський національний університет імені Лесі Українки, 2008)
Речь идет о пьесе “Золотопромышленники” (1887) и ее окончательной редакции – комедии „На золотом дне (1888)”. Пьеса по праву является предшественницей „новой драмы” − пьес чеховского типа. The speech goes about the play „Obtaining gold” (1887) – and about final edition of a comedy „On a gold bottom” (1888). Play under the right precedes „a new drama”, plays Chehov’s type.
Mamin-Sibiriak’s Сomedy „On a Gold Bottom” (Final Edition of the Play „Obtaining Gold”)
Keywords: Мамин-Сибиряк; Mamin-Sibiriak; „Золотопромышленники”; „Obtaining gold”; „На золотом дне”; „On a gold bottom”; пьеса чеховского тип; plays Chehov’s type